Macrophage Trafficking as Key Mediator of Adenine-Induced Kidney Injury - Matheus Correa-Costa; Tárcio Teodoro Braga; Raphael José Ferreira Felizardo; Vinícius Andrade-Oliveira; Katia Regina Perez; Iolanda Midea Cuccovia; Meire Ioshie Hiyane; João Santana da Silva; Niels Olsen Saraiva Câmara (Hindawi Limited, 2014)
Macrophages play a special role in the onset of several diseases, including acute and chronic kidney injuries. In this sense, tubule interstitial nephritis (TIN) represents an underestimated insult, which can be triggered by different stimuli and, in the absence of a proper regulation, can lead to fibrosis deposition. Based on this perception, we evaluated the participation of macrophage recruitment in the development of TIN. Initially, we provided adenine-enriched food to WT and searched for macrophage presence and action in the kidney. Also, a group of animals were depleted of macrophages with the clodronate liposome while receiving adenine-enriched diet. We collected blood and renal tissue from these animals and renal function, inflammation, and fibrosis were evaluated. We observed higher expression of chemokines in the kidneys of adenine-fed mice and a substantial protection when macrophages were depleted. Then, we specifically investigated the role of some key chemokines, CCR5 and CCL3, in this TIN experimental model. Interestingly, CCR5 KO and CCL3 KO animals showed less renal dysfunction and a decreased proinflammatory profile. Furthermore, in those animals, there was less profibrotic signaling. In conclusion, we can suggest that macrophage infiltration is important for the onset of renal injury in the adenine-induced TIN.